2010
DOI: 10.1152/physiolgenomics.00174.2009
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump coronary artery bypass surgery is associated with fewer gene expression changes in the human myocardium in comparison with on-pump surgery

Abstract: Ghorbel MT, Cherif M, Mokhtari A, Bruno VD, Caputo M, Angelini GD. Off-pump coronary artery bypass surgery is associated with fewer gene expression changes in the human myocardium in comparison with on-pump surgery. Physiol Genomics 42: 67-75, 2010. First published March 23, 2010 doi:10.1152/physiolgenomics.00174.2009.-Offpump coronary artery bypass surgery reduces the myocardial injury associated with on pump surgery with cardiopulmonary bypass (CPB) and ischemic-cardioplegic arrest (CA). We sought to find a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…CPB with ischemic arrest is known to induce the release of cytokines and chemokines involved in cellular homeostasis, thrombosis, and coagulation; oxidative stress; adhesion of blood cell elements to the endothelium; and neuroendocrine stress responses; all of these may contribute to myocardial injury (208,209). Controlled reperfusion strategies during CPB, involving prolonged reperfusion with warm-blood cardioplegia in conjunction with metabolic enhancers, are rarely used in lieu of more routine methods of preservation (e.g., asystolic arrest, anterograde or retrograde blood cardioplegia during aortic crossclamping).…”
Section: Intraoperative Tee: Recommendationsmentioning
confidence: 99%
“…CPB with ischemic arrest is known to induce the release of cytokines and chemokines involved in cellular homeostasis, thrombosis, and coagulation; oxidative stress; adhesion of blood cell elements to the endothelium; and neuroendocrine stress responses; all of these may contribute to myocardial injury (208,209). Controlled reperfusion strategies during CPB, involving prolonged reperfusion with warm-blood cardioplegia in conjunction with metabolic enhancers, are rarely used in lieu of more routine methods of preservation (e.g., asystolic arrest, anterograde or retrograde blood cardioplegia during aortic crossclamping).…”
Section: Intraoperative Tee: Recommendationsmentioning
confidence: 99%
“…In the last years, several studies have demonstrated the value of myocardium transcriptome analysis for elucidating the molecular mechanisms underlying cardiovascular disease pathogenesis and identifying novel biomarkers for prognostic and therapeutic purposes [10,[13][14][15][16][17]30]. In this study, we carry out the first comparative gene expression profiling of ToF and ASD right atrial specimens before and after surgery with CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that evaluated the circulating levels of proinflammatory cytokines (IL‐6, ‐8, and ‐10) after off‐ and on‐pump‐ surgery reported contradictory results 14, 18, 19, 20, 21, 22…”
Section: Differences In Systemic Inflammatory Reaction and Platelet/cmentioning
confidence: 99%